An aerothermal study of the influence of squealer width and height near a HP turbine blade - Senel, C.B.; Maral, H.; Kavurmacioglu, L.A.; Camci, C. (Elsevier BV, 2018)
Abstract Highly three-dimensional and complex flow structure within the tip gap of an axial flow turbine is a substantial source of aerodynamic loss and heat transfer due to the interaction between the tip leakage vortex, secondary flows and the main passage flow. Most contemporary shroudless high pressure (HP) turbine designs employ squealer tips for durability, structural, aerodynamic design and heat transfer reasons. The present research deals with the influence of squealer width and height on the aerothermal performance of a HP turbine blade. In this study, four different squealer heights and seven squealer width values are investigated using a computational approach for an axial turbine blade depicting an E 3 “Energy Efficient Engine” design. The specific HP turbine airfoil under investigation is identical to the rotor tip profile of the Axial Flow Turbine Research Facility (AFTRF) of the Pennsylvania State University. Numerical calculations are performed by solving the three-dimensional, steady and turbulent form of the Reynolds-Averaged Navier-Stokes (RANS) equations. A two-equation turbulence model, Shear Stress Transport (SST) k-ω is used in the present set of calculations. The current numerical predictions show a very good agreement with the extensive aerodynamic measurements obtained in the nozzle guide vane passages of AFTRF. The results indicate that determining proper squealer width and height is crucial to obtain better aerothermal performance in the form of reduced aerodynamic loss and heat transfer to the tip platform. Extensive numerical analysis within the tip gap reveals that increasing squealer height and reducing squealer width increases cavity volume leading to enlarged vortical structures near the pressure side and suction side of the cavity. Because of this enhanced vortical activity in the tip cavity, a blockage to the incoming pass-over flow is introduced and as a result tip leakage mass flow rate is reduced. While the tip leakage flow rate tends to decrease with increased height and reduced width, there is a strong effect from the squealer width and height combination due to the presence of complex interactions in the tip gap region. From a heat transfer point of view, decreasing squealer width and increasing squealer height noticeably reduces the overall Nu ‾ on the blade tip platform. Nu ‾ on the cavity floor, blade tip and squealer side walls are reduced depending on the increasing height and decreasing width values.